Commonly cited incentives in the community implementation of the emergency maternal and newborn care study in western Kenya - Gisore, P (Makerere Medical School, 2013)
BACKGROUND: Mortality of mothers and newborns is an important public health problem in low-income countries. In the rural setting, implementation of community based education and mobilization are strategies that have sought to reduce these mortalities. Frequently such approaches rely on volunteers within each community. OBJECTIVE: To assess the perceptions of the community volunteers in rural Kenya as they implemented the EmONC program and to identify the incentives that could result in their sustained engagement in the project. METHOD: A community-based cross sectional survey was administered to all volunteers involved in the study. Data were collected using a self-administered supervision tool from all the 881 volunteers. RESULTS: 881 surveys were completed. 769 respondents requested some form of incentive; 200 (26%) were for monetary allowance, 149 (19.4%) were for a bicycle to be used for transportation, 119 (15.5%) were for uniforms for identification, 88 (11.4%) were for provision of training materials, 81(10.5%) were for training in Home based Life Saving Skills (HBLSS), 57(7.4%) were for provision of first AID kits, and 39(5%) were for provision of training more facilitators, 36(4.7%) were for provision of free medication. CONCLUSION: Monetary allowances, improved transportation and some sort of identification are the main incentives cited by the respondents in this context.